Inclusão e transdisciplinaridade : limites e possibilidades para a construção de uma rede de apoio ao professor, no contexto dos anos iniciais na educação básica - Arieta, Mariana de Souza (2022)
This dissertation is the result of a qualitative research of the case study type, carried out between the years 2020 and 2021, in the context of a global pandemic, of covid-19. In this way, the explicit results were aimed to identify the comprehension attributed to inclusion by the Marist Network, as well as the guidelines related to inclusive processes, according to institutional documents, describe and analyze the actions that characterize the work of professionals at Colégio Marista Rosário who work in inclusive processes at school, understanding how these members articulate themselves when conducting work, explore how institutional, technical, interpersonal and subjective aspects influence the formation of a transdisciplinary performance when conducting inclusive processes, specifically analyzing the role of Educational Advisors in the articulation of teamwork. In order to achieve its intention, it was decided to carry out a State of Knowledge, aiming to seek studies on the themes, contributing to the construction of the theoretical framework and evidencing the originality and social relevance of the research. This dissertation addresses theoretical frameworks related to the themes of Inclusion and Transdisciplinarity and details the stages of the research carried out. The data collected through the analysis of institutional documents and a survey - exploratory research - were analyzed through the assumptions of Lawrence Bardin’s Content Analysis (2011), which served as a foundation for the construction of an analytical grid, which gave rise to a new survey, containing statements classified by degree of agreement (Lickert’s Scale). From the result analysis, it was noticed that the elements pointed out by the professionals, can be facilitators or constraint for the transdisciplinary performance in teams, being directly related to the personal and institutional placement, with regard to personal openness, interpersonal relationships, professional maturity and institutional hierarchy, that can be explored if the purpose is to seek a more inclusive and less excluding school culture.